Obesity and effects of dapagliflozin on cardiovascular and renal outcomes in patients with type 2 diabetes mellitus in the DECLARE–TIMI 58 trial . (24th August 2021) - Oyama, Kazuma; Raz, Itamar; Cahn, Avivit; Kuder, Julia; Murphy, Sabina A; Bhatt, Deepak L; Leiter, Lawrence A; McGuire, Darren K; Wilding, John P H; Park, Kyong Soo; Goudev, Assen; Diaz, Rafael; et al.
Abstract: Aims : We investigated the associations between obesity, cardiorenal events, and benefits of dapagliflozin in patients with type 2 diabetes mellitus (T2DM). Methods and results : DECLARE–TIMI 58 randomized patients with T2DM and either atherosclerotic cardiovascular (CV) disease or multiple risk factors to dapagliflozin vs. placebo. Patients were stratified by body mass index (BMI, kg/m 2 ): normal (18.5 to <25), overweight (25 to <30), moderately obese (30 to <35), severely obese (35 to <40), and very-severely obese (≥40). Outcomes analysed were CV death, hospitalization for heart failure (HHF), renal-specific composite outcome, and atrial fibrillation or flutter (AF/AFL). Of 17 134 patients, 9.0% had a normal BMI, 31.5% were overweight, 32.4% were moderately, 17.2% severely, and 9.8% were very-severely obese. Higher BMI was associated with a higher adjusted risk of HHF and AF/AFL (hazard ratio 1.30 and 1.28, respectively, per 5 kg/m 2 ; P  < 0.001 for all). Dapagliflozin reduced body weight by similar relative amounts consistently across BMI categories (percent difference: −1.9 to −2.4%). Although relative risk reductions in CV and renal-specific composite outcomes with dapagliflozin did not significantly differ across the range of BMI ( P for interaction ≥0.20 for all outcomes), obese patients (BMI ≥ 30 kg/m 2 ) tended to derive greater absolute risk reduction in HHF and AF/AFL ( P for interaction 0.02 and 0.09, respectively) than non-obese patients. Conclusions : In DECLARE–TIMI 58, patients with T2DM and higher BMI were more likely to have HHF and AF/AFL. Whereas relative risk reductions in CV and renal outcomes with dapagliflozin were generally consistent across the range of BMI, absolute risk reduction in obesity-related outcomes including HHF and AF/AFL tended to be larger in obese patients with T2DM. Clinical trial registration: URL: https://www.clinicaltrials.gov . Unique identifiers: NCT01730534. Graphical Abstract: